Development of Stimuli-Responsive Suprasomes for Therapeutics, Temporal Catalysis and Communication - Prusty, Biswa Mohan (My University, 2025)
This thesis focuses on the design and functional exploration of suprasomes, supramolecular assemblies formed through non covalent host guest interactions, and their applications in biomimetic and stimuli responsive systems. Beginning with fundamental aspects of supramolecular host guest chemistry, the work demonstrates the development of beta cyclodextrin based suprasomes for Zn2+ triggered antibiotic delivery with tunable antibacterial activity. The thesis further addresses a key challenge in therapeutic ion transport by designing supramolecular ion channel systems responsive to divalent metal ions such as Zn2+. Going ahead, Zn2+ induced suprasomal transformation into transient supracubes is explored, enabling catalytic esterase activity and chemical communication between vesicular systems. Finally, a nature inspired, temporally gated, multistimuli responsive suprasome is presented, capable of photonic memory storage and inter vesicle communication. Collectively, this work establishes suprasomes as versatile platforms for drug delivery, controlled catalysis, information processing, and communication in synthetic systems.
Manna, Debasis